PENGARUH SELF EFFICACY TERHADAP PENYESUAIAN AKADEMIK MAHASISWA - Fina Sopiyanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2011)
This research specifically observes student psychological personal factor, which is assumed that it influences their academic adaptation. Psychological factor which will be observed is self efficacy, i.e., someone’s conviction about their skill in managing and performing an action for producing an expected performance (Bandura; 1997). The research design applies correlation design, linier regression analysis, i.e., the other way to describe and evaluate the correlation between some variables with assumption that one variable has the role as criterion variable, and the other variable has the role as predictor variable. With linier regression, it is enabled to predict a variable basing on a value from predictor. The analysis result of data shows that correlation coefficient of independent variable = 0.809 and R2 = 0.646. it shows that 64,6 percent of student academic adjustment variety is determined by self efficacy variety, whereas 35,4 percent is determined by the other variables.